Pertumbuhan dan Sekresi Protein Hasil Kultur Primer Sel-Sel Serebrum Anak Tikus (IN VITRO GROWTH AND PROTEIN SECRETION OF NEWBORN RAT CEREBRAL PRIMARY CELLS CULTURE) - Djuwita, Ita; Riyacumala, Vivit; Mohamad, Kusdiantoro; Prasetyaningtijas, Wahono Esthi; ., Nurhidayat (Jurnal Veteriner, 2013)
The objective of this study was to identify the proliferation and differentiation of mice cerebrum cellsand its protein product. Research has been conducted on in vitro growth of three days old rat cerebrum cellsin Dulbecco’s Modified Eagle Medium (DMEM) containing 10% Amino Acid Non Essential (AANE), 10%Fetal Bovine Serum (FBS), 3mM NaHCO3, 50 mg/ml gentamycin, and supplemented with and without 5mg/ml insulin, 10 mg/ml transferin, 5 mg/ml selenium (ITS). Culture was done in 5% CO2, then incubatedat 37oC until 90% confluent. Identification were done on cell proliferation and population doubling time(PDT), number of neuron and glial cells, length of axon and dendrit, and protein secretion. The number andlength of neuronal cells were calculated by using hemocytometer and eyepiece micrometer, respectivelly.Protein secreted into culture medium, designed as conditioned medium (CM) was analysized using sodiumdodecyl sulfate–polyacrilamide gel electrophoresis (SDS-PAGE) method. Quantitative data were analyzedusing statistical T-test on Minitab program. In vitro culture of rat cerebrum cells showed two types of cellsincluding nerve cells of bipolar and multipolar neurons and glial cells including astrocyte (the fibrous andprotoplasmic), oligodendrocyte, and microglia. Supplementation of ITS into the culture medium increasedthe cell proliferation rate (P<0.05) with lower PDT, and quantitatively, the 30 kDa secreted protein asindicated by the higher intensity of the protein band.
Keywords: proliferation, protein secretion, neuronal cells, in vitro culture